Pemberdayaan Komunitas Lokal melalui Strategi Multidisiplin: Model Pengabdian Masyarakat di Songkhla, Thailand - Amri, Abrar; Putri , Cut Widy Aulia; Soufyan, Dara Angreka; Ringo, Liston Siringo (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
Community service is an opportunity for academic communities to contribute to societal development through empowerment initiatives without expecting specific compensation. As a pillar of the Tri Dharma of Higher Education, community service plays a vital role in enhancing the potential and capabilities of local communities in education, knowledge, skills, and technology. This program focuses on empowering the local community in Songkhla, Thailand, using multidisciplinary strategies to address various challenges. Implemented at the Al-Hidayah Waqaf Foundation for Education and Social Development, the activities were conducted in a hybrid format, combining one day of in-person sessions and two days of online sessions. The program emphasized collaboration between universities and international partners to deliver impactful knowledge and skills. Key results included increased community knowledge, the application of new skills, and strengthened partnerships across sectors. This community empowerment initiative serves as a model for sustainable development, fostering independence and addressing global issues such as poverty, education gaps, and health crises through innovative and collaborative approaches.